2006 Sixth European Dependable Computing Conference 2006
DOI: 10.1109/edcc.2006.20
|View full text |Cite
|
Sign up to set email alerts
|

Rephrasing Rules for Off-The-Shelf SQL Database Servers

Abstract: We have reported previously [1] results of a study with a sample of bug reports from four off-the-shelf SQL servers. We checked whether these bugs caused failures in more than one server. We found that very few bugs caused failures in two servers and none caused failures in more than two. This would suggest a fault-tolerant server built with diverse off-the-shelf servers would be a prudent choice for improving failure detection. To study other aspects of fault tolerance, namely failure diagnosis and state reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…with translation, as we have shown in [22]) and/or clients to be limited to using a common subset among the features of the diverse DBMS products. In addition, many aspects of database operation are specified in a nondeterministic fashion, making the goal of ensuring consistency among replicas difficult, even with sameproduct replication and more so with diverse replication.…”
Section: Diversitymentioning
confidence: 90%
See 3 more Smart Citations
“…with translation, as we have shown in [22]) and/or clients to be limited to using a common subset among the features of the diverse DBMS products. In addition, many aspects of database operation are specified in a nondeterministic fashion, making the goal of ensuring consistency among replicas difficult, even with sameproduct replication and more so with diverse replication.…”
Section: Diversitymentioning
confidence: 90%
“…Thanks to the redundancy in the SQL language, a sequence of one or more SQL statements can be "rephrased" into a different but logically equivalent sequence to produce redundant executions, reducing the risk of a failure being repeated when the rephrased sequence is executed on the same or another replica of even the same DBMS product. Two of the present authors have reported in [22] a set of "rephrasing rules" that would tolerate at least 60 percent of the bugs examined in our studies. Another possibility is varying the "hints" to the "query optimizer" of the DBMS that are included with SQL statements.…”
Section: Diversitymentioning
confidence: 93%
See 2 more Smart Citations
“…Also we have observed in earlier research [4], [3] that AB-faults can fail in different ways in the two DBMS products, and hence can be detected (and potentially corrected [16]). As a result, the estimates that we get using our models for the reliability benefits of diversity will most probably be underestimates: the true benefits may be higher.…”
Section: Discussionmentioning
confidence: 99%